Evaluation of Antimicrobial Compound Effect from Senna alata Linn. Against Multiple Antibiotic Resistance (MAR) Bacteria from Environment - Scholastica Ramih, Bunya (Universiti Malaysia Sarawak, 2024)
The increasing prevalence of multiple antibiotic-resistant (MAR) bacteria has increased the interest in exploring the potential of medicinal plants as a source of antimicrobial agents. Senna alata Linn. commonly known as “gelenggang” and “daun kurap” in Malaysia, is a medicinal plant with various ethnomedical uses and biological features. This study evaluated the antibacterial activity of leaves, stems, and roots against MAR bacteria from the environment, Enterococcus sp., and Mammaliicoccus sp. The bacteria used in this study were obtained from the environmental bacterial stock provided by the Molecular Laboratory, Institute of Biodiversity and Environmental Conservation, UNIMAS and Department of Animal Science and Fisheries, Universiti Putra Malaysia, Bintulu Campus. From the antibiotic susceptibility test, the MAR value Enterococcus sp. was 0.83, which showed resistance against erythromycin, tetracycline, norfloxacin, chloramphenicol and vancomycin. Meanwhile, in Mammaliicoccus sp., the MAR value was 0.40, and resistant towards piperacillin, aztreonam, ceftazidime and penicillin. The extraction methods used were soxhlet extraction (SE) and ultrasonic-assisted extraction (UAE), accompanied by ethanol, chloroform and hexane as the choice of solvent. Among all plant parts, the soxhlet and ethanol extracts produced higher yields. However, in the next assay, hexane was removed as it gave a very low yield and was not suitable as most assays needed a high extract concentration. On the other hand, leaves extract showed a greater yield than stems and roots. S. alata extracts were also tested for their total phenolic content (TPC) and total flavonoid content (TFC) using Folin-Ciocalteu and aluminium chloride methods, respectively. Both TPC and TFC were exhibited the highest by the leaves of ultrasonic and chloroform extract, UAE-Chlo-L (TPC=117.44±2.78 mg GAE/g DW, TFC=568.78±24.44 mg QE/g DW), followed by the leaves of soxhlet and chloroform extract, SE-Chlo-L. (TPC=80.39±6.60 mg GAE/g DW, TFC=406.44±7.41 mg QE/g DW). In antibacterial activity using agar well diffusion assay, most of the extracts, especially from soxhlet extraction, were more sensitive and inhibited higher in the Mammaliicoccus sp. compared to Enterococcus sp. The largest inhibition towards Mammaliicoccus sp. was exhibited by SE-Chlo-S (15.00 ± 0.00 mm) with minimum inhibitory concentration and minimum bactericidal concentration at 0.39062 mg/mL and 3.125 mg/mL, respectively. Based on the minimum inhibitory concentration/minimum bactericidal concentration ratio conducted, all the extracts in this study showed potential as bactericidal agents. Besides, the extracts' bioactive compounds associated with antibacterial activity were identified using thin-layer chromatography-direct bioautography (TLC-DB) assay and gas chromatography-mass spectrometry (GC-MS) analysis. Among many spots identified on the TLC plates, only L2 (Rf = 0.47), S2 (Rf = 0.40,) and R1 (Rf =0.42) showed inhibition towards tested bacteria. Various bioactive compounds such as Phenol, 3,5-bis(1,1-dimethylethyl)-, Cholest-5-en-3-ol (3.beta.)-, carbonochloridate, Neophytadiene, Decane, 3,7-dimethyl-, Dodecane, 2,6,11-trimethyl-, 2-Pentadecanone, 6,10,14-trimethyl-, and many other compounds were identified. The findings in this study indicated that S. alata possessed antibacterial activities besides having unique bioactive compounds that can be used as a potential antibacterial agent for the production of new drugs in combatting the multiple antibiotic resistance issues in bacteria, particularly bacteria from the environment.